Description of Mother's Knowledge about Influence Foods that Contain Sucrose the Occurrence of Dental Caries in Pampang Health Center Makassar City - Djunaedi, Djunaedi; Suprapti, Isma; Nawangwulan, Kurniawati; Nurnainah, Nurnainah; Claartje, Masrikat Maya Diana; Zafera Adam, Jeanne d’Arc; Sangkala, Sangkala (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Food is something that affects the condition in the mouth locally during mastication and after being swallowed will affect the growth and development of the pre and post tooth eruption. Dental disease that is often encountered is caries. The process of caries is caused by food debris attached to the surface of the teeth and if leftovers are not cleaned, acids will form so that bacteria will take place quickly and cause dental caries. The sample used in the study was 30 respondents who came for treatment at the Pampang Health Center, Makassar City. This research was conducted at the Pampang Health Center, Makassar City. The sample method used in this research was purposive sampling, which was taken using criteria, and the data taken for analysis was primary data obtained by giving questionnaires and dental examinations using observation sheets to patients who had came for treatment at the puskesmas. This research was a descriptive study, namely to describe the mother's knowledge about the effect of sucrose-containing foods on the occurrence of dental caries at the Pampang Health Center, Makassar City.